Islam and the everyday world: public policy dilemmas. Edited by Sohrab Behdad and Farhad Nomani (Abingdon: Routledge, 2006), 240 pp. Price HB £70.00. ISBN 0–415–36823–5 - Haneef, Mohamed Aslam (Oxford University Press, 2008)
Reference materials related to public policy discourse within an Islamic framework are very scarce and the prospect of reviewing a book with this title was very enthusiastically awaited. According to the editors, this volume contains eight updated and revised articles, chosen from contributions written originally for a special issue (1997) of International Journal Review of Comparative Public Policy, and covers areas of economics, human rights, family law, labour law, commercial law, public finance and banking. The introductory article by Behdad places the themes within the context of contemporary Islamic revivalism. He begins by stating how contrasting interpretations of Islam, as represented by two visions of Islamic ideology and their implications for public policy can be traced to the time of the Prophet. Using a Shariati-like approach, Behdad categorizes these visions as one of rebellion vs. order, one that represents a vision of a monotheistic classless society vs. one that represents Islamic capitalism. He uses this division to take the readers through his interpretations of siyāsa or public policy in Islamic history by discussing issues of prices, markets, public interest (maṣlaḥa), the reform movements at the turn of the twentieth century to the Islamic revolution in Iran. Maybe true to his own vision, the author laments how the rebellious, classless vision of Abū Dharr has always been countered by a class based ‘Pax Islamica’. It is this dynamic that, the author contends, needs to be studied by those who want to present Islam as a social order, having public policy dimensions and which forms the discussions of the other authors in this volume.